1981
DOI: 10.1111/j.1398-9995.1981.tb01830.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic, Adjuvant and Permeability Enhancing Properties of Melittin in Mice

Abstract: Melittin, a mast cell lytic agent which comprises 50% of the protein content of bee venom, may be responsible for some of the severe reactions produced by bee stings in allergic and non-allergic individuals. We therefore investigated some of the biologic properties of this molecule in mice and found that repeated intradermal injections of melittin without adjuvant induced IgE formation in mice. In addition, melittin as well as another surfactant, saponin, were potent adjuvants for IgE formation in mice when mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…The authors' conclusion was that there was no correlation between hemolytic activity, lethality, and adjuvant activity. No specific IgE was induced with any of these four fractions in contrast to other reports using Quil A [66], Gypsophilia saponins [67], or saponins from un-named sources [68,69] all of which have shown increased levels of IgE after the addition of saponin to vaccines.…”
Section: Toxicity Of Saponins Iscoms and Iscom Matrixcontrasting
confidence: 50%
“…The authors' conclusion was that there was no correlation between hemolytic activity, lethality, and adjuvant activity. No specific IgE was induced with any of these four fractions in contrast to other reports using Quil A [66], Gypsophilia saponins [67], or saponins from un-named sources [68,69] all of which have shown increased levels of IgE after the addition of saponin to vaccines.…”
Section: Toxicity Of Saponins Iscoms and Iscom Matrixcontrasting
confidence: 50%
“…4A). Bee venom and purified melittin can also be used as adjuvant to induce antigen-specific IgE production to an admixed antigen, such as ovalbumin (OVA) (21). However, we found that caspase-1 was also dispensable for the induction of anti-OVA IgE after immunization with OVA admixed with melittin (Fig.…”
Section: Resultsmentioning
confidence: 49%
“…In models of inflammation induced by the venoms of various species, leukocyte recruitment [21][22][23], protein extravasation and edema formation [24][25][26] have also been observed.…”
Section: Discussionmentioning
confidence: 95%